Creative Integrated Methodological Approaches in Teaching Physics - Mamajonov Xoshimjon Abdumalikovich; Tillaboyev Azlarxon Magbarxonovich – (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2026)
Abstract: In the context of modern educational transformation, the development of students’ creative and critical thinking skills has become a priority. This study examines the role of creative integrated methodological approaches in teaching physics. The research focuses on how combining interdisciplinary integration with creativity-oriented teaching strategies enhances students’ engagement, conceptual understanding, and problem-solving abilities. A mixed-methods design was employed, including experimental teaching, surveys, and performance assessments. The results demonstrate that creative integration significantly improves learning outcomes and fosters innovative thinking. The study also identifies key methodological principles and challenges in implementing such approaches. Recommendations are provided for educators aiming to modernize physics instruction.